Remembering genocide in Namibia - Reitz, Núrel Bahí (Working papers, 2021)
The paper seeks to provide an overview of memory politics in Namibia. Most of the German media and political debates addressing the genocide committed against the Herero, Nama, Damara, and San by the German Schutztruppen during the 1904-1908 counterinsurgency in the former German South-West Africa are focused on possible legal implications. Consequences of 'our' ways of dealing with the past for 'their' domestic relations and memory cultural struggles in Namibia tend to be overlooked. Our paper intends to foster a more thorough understanding of foreign policy decisions' implications for the target societies' struggle for recognition. To that end, we first outline key actors in the Namibian memory politics and present contested historical narratives that can be found in the different actor groups. In a second step practices surrounding three physical memory sites in the Namibian mnemoscape are analysed, and memorialisation through commemoration is discussed. Finally, the paper draws attention to the necessity of including as well hitherto marginalized societal actors as controversial topics in memory culture debates to create an arena for productive contestation.